Imunocastração e ractopamina na dieta de suínos: implicações na qualidade de carne fresca e melhorada por injeção (enhancement) - Iocca, Andréia Fernanda Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Several technological strategies have been used by pork industry for over three decades with investment in genetics selection, nutrition and management, providing greater efficiency in animal production. The addition of ractopamine (RAC) in the finishing diet has been widely used to improve the growth performance of the animal and immunocastration is a painless alternative method of inhibition from sexual compounds in carcass fat and accumulation decrease of pheromones. More than two thirds of the pork produced worldwide is consumed through processed foods, so it is necessary to understand the effects of technologies applied in pork production in the quality of these products. Males and gilts pigs (FE) from two different farms and different crossbreed [Time Topigs 40 male x female, gene Topigs (n = 450) and male AGPIC 337 x CB 22 females, gene Agroceres (n = 180)] were randomly selected. Half of the male pigs were castrated physically (CF) and the other half were not (boar). In the production phase boar were immunocastrated (IM). Half of the pigs (FE, CF and IM) received treatment with RAC (7.5 mg / kg) for three weeks before slaughter and the other half conventional diet (without RAC). Pigs of each crossbred were slaughtered in different slaughterhouses and the carcasses were chilled for 24 hours at 4°C. 30 loins were selected, coming from the right half-carcasses of each farm, for fresh evaluations and processing of improved by injection loins (enhancement). Several parameters were evaluated in fresh pork loin and enhanced pork loin: pH, color (L *, a *, b *, C, h °), texture by shearing force and chemical composition; enhanced by injection loins: yield, purge loss (PPE), cooking loss (PPC), microbiological safety standards and sensory analysis. For the A crossbred was the RAC effect and about sex only in the shear force, where treatments with RAC and immunocastration had less tender loins. The RAC and the IM did not affect the ...

Diversas estratégias tecnológicas têm sido utilizadas pelo setor suinícola em pouco mais de três décadas com investimento em seleção genética, manejo e nutrição, propiciando maior eficiência na produção animal. A adição de ractopamina (RAC) na dieta de suínos em terminação tem sido amplamente utilizada para melhorar o desempenho zootécnico do animal e a imunocastração é um método alternativo e indolor de inibição dos compostos sexuais na gordura das carcaças e redução do acúmulo de feromônios. Mais de 2/3 da carne suína produzida no mundo é consumida por meio de produtos processados, sendo necessário compreender os efeitos das tecnologias empregadas na produção suinícola na qualidade destes produtos. Suínos machos e fêmeas (FE) de duas diferentes granjas comerciais e distintos cruzamentos genéticos [Tempo, macho x Topigs 40, fêmea, genética Topigs® (n = 450) e AGPIC 337 macho x CB 22 fêmeas, genética Agroceres® (n = 180)] foram aleatoriamente selecionados. Metade dos suínos machos foi castrado fisicamente (CF) e a outra metade não (inteiros). Na fase produtiva os suínos inteiros foram imunocastrados (IM). Metade dos suínos (FE, CF e IM) receberam o tratamento com RAC (7,5 mg/kg) durante três semanas antes do abate e a outra metade dieta convencional (sem RAC). Suínos de cada genética foram abatidos em diferentes abatedouros comerciais e as carcaças foram resfriadas por 24 horas a 4°C. Foram selecionadas 30 lombos, oriundos de meias carcaças direitas de cada granja, para as avaliações in natura e processamento dos lombos melhorados por injeção. Foram avaliados diversos parâmetros na carne in natura e após processamento: pH, cor (L*, a*, b*, C, h°), textura por força de cisalhamento e composição centesimal; e nos lombos melhorados por injeção: rendimento, perda de peso por exsudação (PPE), perda de peso na cocção (PPC), padrões de segurança microbiológicas e análise ...
Keywords: Tecnologia de alimentos; Carne de porco - Industria; Suino - Alimentação e rações; Carne de porco - Qualidade; Food technology